2009
DOI: 10.4103/0019-5154.55645
|View full text |Cite
|
Sign up to set email alerts
|

Hematohidrosis - A rare clinical phenomenon

Abstract: Hematohidrosis is a very rare condition of sweating blood. A case of hematohidrosis is reported. There are only few reports in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 1 publication
1
20
1
Order By: Relevance
“…Benzidine test is an important tool in diagnosis, where hemoglobin in blood reacts with hydrogen peroxide-liberating oxygen, which then reacts with organic reagent producing a green to blue colored compound. [ 7 ] Peripheral blood smear confirms that the blood is of human origin in our case.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Benzidine test is an important tool in diagnosis, where hemoglobin in blood reacts with hydrogen peroxide-liberating oxygen, which then reacts with organic reagent producing a green to blue colored compound. [ 7 ] Peripheral blood smear confirms that the blood is of human origin in our case.…”
Section: Discussionsupporting
confidence: 78%
“…One hypothesis proposed for etiopathogenesis of hematohidrosis, as suggested by some authors,[ 7 ] is that multiple blood vessels present in a net-like form around the sweat gland constrict under pressure of stress. As the anxiety passes out, the blood vessels dilate to the point of rupture.…”
Section: Discussionmentioning
confidence: 99%
“…In other side, Manonukul suggested that there are maybe some dermal defects or some distinctive substances damaged the vessels supplying sweat glands [3]. Other researchers believed that this phenomenon could be related to some chronic underlying disease, namely Hemochromatosis [4,5]. Lack of evidence basis led to the difficulty in determination the cause of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…The etiopathogenesis proposed by few authors is that blood vessels around the sweat glands constrict under stress. [ 5 ] As the anxiety increases, the blood vessels rupture. The blood extravasates into the sweat glands presenting as droplets of blood mixed with sweat.…”
Section: Discussionmentioning
confidence: 99%